Karyotypes of eight species of Leptodactylus (Anura, Leptodactylidae) with a description of a new karyotype for the genus - Amaro-Ghilardi, Renata Cecília; Skuk, Gabriel; Sá, Rafael O. de; Rodrigues, Miguel Trefaut; Yonenaga-Yassuda, Yatiyo (Phyllomedusa: Journal of Herpetology, 2006)
Eight species of the Neotropical genus Leptodactylus were karyologically studied: seven of them (L. gracilis, L. mystacinus, L. petersii, L. pustulatus, L. macrosternum, L. ocellatus, L. labyrinthicus) presented 2n=22 and L. silvanimbus showed a distinctive karyotype with 2n=24. Nucleolar organizer regions (Ag-NORs) were detected in two different pairs of chromosomes: pair 4 at the proximal region of the long arm of one individual of L. mystacinus from São Paulo state and of L. petersii; and pair 8 of all other species (located terminally at the short arm of L. silvanimbus, L. ocellatus, L. macrosternum, L. pustulatus, and L. labyrinthicus; interstitially at the short arm in L. gracilis; and at the long arm in L. mystacinus from Mato Grosso state). The diploid number reported here for L. silvanimbus shared with Scythrophrys and Paratelmatobius could represent the ancestral chromosome number for Leptodactylus (sensu Frost et al. 2006); in this case the 2n=22 karyotypes would then represent the derivative condition for the genus. Nevertheless, the distinctive karyotype of L. silvanimbus lead us to preclude a final decision on its relationships. Additional studies including morphological and molecular approaches are needed in order to clarify the phylogenetic position of L. silvanimbus.